Case Report: Gastrointestinal PEComa With TFE3 Rearrangement Treated With Anti-VEGFR TKI Apatinib - Xu, Jiaming; Gong, Xiao-Lei; Wu, Huanwen; Zhao, Lin (Frontiers in Oncology, 2020)
Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors. Unresectable malignant PEComas with TFE-3 rearrangement have no recommended therapy to date. Here, we report the first case of malignant gastrointestinal PEComa with TFE3 rearrangement which has a response to the targeted therapy of an anti-VEGFR tyrosine kinase inhibitor (TKI), apatinb. A 31-year-old female was diagnosed with malignant gastrointestinal PEComa with TFE3 arrangement and hepatic metastases. A resection of the giant retroperitoneal mass was performed. The patient received the anti-VEGFR TKI apatinib to treat the hepatic metastasis. The tumor remained stable during apatinib treatment and the progression-free survival (PFS) lasted about 7 months. This case suggests that targeting the VEGF/VEGFR signaling pathway may be an essential new therapeutic choice for TFE3-associated malignant PEComas.